Antenatal Care (ANC) as an Early Health Detection Program for Pregnant Women: Antenatal Care (ANC) sebagai Upaya Deteksi Dini Kesehatan Ibu Hamil - R.A. Helda Puspitasari; Ayu Dewi Nastiti; Dwining Handayani (KHD Production, 2024)
This community engagement aim is to increase the knowledge of pregnant women and inform that the importance of ANC is to undergo a healthy pregnancy, and give birth to a healthy baby and monitor early maternal and fetal health, in the Tengger Region, East Java. The method begins with measuring the knowledge of pregnant women about Antenatal Care then continued with Antenatal Care examination then continued with counseling with the method of discussion, lecture and question and answer with respondents at the end of the post-test. Community service activities were carried out on 20 pregnant women. The results were followed by an independent t-test statistical test of SPSS software to measure the knowledge of pregnant women. The results of pretest and posttest measurements carried out are that there is an increase in knowledge, before 50%, after counseling (post-test) knowledge becomes good 75%. The conclusion is that there is an effect of counseling on pregnant women who experience an increase in knowledge by 75%.